E-WOM and Satisfaction Level’s Effects on Massive Open Online Course Repurchase Intention by Generation-Z - Kuswardi, Joshua; Lim, Sanny (International Journal Labs, 2023)
Background: The Massive Open Online Course (MOOC) is an innovation that is experiencing rapid growth in the world in the field of technology-based education, including in Indonesia. Aim: This study aims to analyze the factors that influence repurchasing interest in one of the Massive Open Online Courses (Skill Academy by Ruangguru) in Indonesia. Method: The factors analyzed include convenience, usefulness, content class quality, service quality, and satisfaction levels as moderation, as well as Electronic - Word of Mouth (E-WOM). This study used quantitative methods and purposive sampling with 200 samples collected. Data processing using PLS-SEM. Findings: The quality of class content in the MOOC learning system does not increase user satisfaction, but a high level of user’s satisfaction and the positive influence of E-WOM can increase the repurchase interest of Generation Z users in Jakarta.